Semen characteristics of individuals before and after Covishield™ vaccination. Issue 3 (22nd September 2022) - Meitei, Huidrom Yaiphaba; Uppangala, Shubhashree; Lakshmi R, Vani; Kalthur, Guruprasad; Adiga, Satish Kumar
Abstract : Concern about fertility impairment after vaccination is one of the reasons for vaccine hesitancy in the population. This retrospective observational study aims to understand the impact of Covishield™ (ChAdOx1 nCoV-19 corona virus vaccine, recombinant) COVID-19 vaccination on ejaculate quality in 53 patients undergoing semen analysis between 2018 and 2021. A baseline semen profile was recorded from the subjects during their visit before the vaccination for fertility work-up. Follow-up ejaculates were provided approximately 82 (Q1: 37, Q3: 124) days after the second dose of vaccination. Semen characteristics such as volume, sperm concentration, sperm motility, and morphological abnormalities were recorded. Of the 53 subjects, 33 (62%) had semen characteristics above the World Health Organization (WHO) reference. In general, no significant variations in the semen parameters were observed except for a moderate decline in sperm morphology ( P  <  0.05). The baseline semen characteristics in 20 (38%) subjects were below the WHO reference range; however, no significant decline in the ejaculate quality was observed in their follow-up samples. Further, none of the ejaculates in both study groups were azoospermic during the follow-up evaluation. Our results affirm that Covishield TM vaccine is not detrimental to male fertility. Lay summary: Concern about fertility impairment after vaccination is one of the reasons for vaccine hesitancy in the population. This study is aimed at understanding the impact of non-mRNA COVID-19 vaccination on ejaculate quality in 53 patients undergoing semen analysis who received Covishield™ (ChAdOx1 nCoV-19 corona virus vaccine, recombinant) vaccine. No significant variation in the semen characteristics was observed between the baseline and follow-up samples in the vaccinated subjects. Results from this study affirm that Covishield™ vaccination is not detrimental to male fertility.